2009
DOI: 10.1017/s0033291709990717
|View full text |Cite
|
Sign up to set email alerts
|

Neurology out-patients with symptoms unexplained by disease: illness beliefs and financial benefits predict 1-year outcome

Abstract: Background. Patients whose symptoms are ' unexplained by disease ' often have a poor symptomatic outcome after specialist consultation, but we know little about which patient factors predict this. We therefore aimed to determine predictors of poor subjective outcome for new neurology out-patients with symptoms unexplained by disease 1 year after the initial consultation.Method. The Scottish Neurological Symptom Study was a 1-year prospective cohort study of patients referred to secondary care National Health S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 41 publications
2
49
0
3
Order By: Relevance
“…[89]. Receiving healthrelated benefits has a negative effect on outcome [90]. Longer duration of symptoms seems to correlate with negative outcome [91].…”
Section: Treatment and Outcomementioning
confidence: 99%
“…[89]. Receiving healthrelated benefits has a negative effect on outcome [90]. Longer duration of symptoms seems to correlate with negative outcome [91].…”
Section: Treatment and Outcomementioning
confidence: 99%
“…For instance, studies in epilepsy have demonstrated that illness perceptions are related to clinically important behaviours (such as medical adherence) and explain a greater proportion of the variance of anxiety measures and people's ability to cope with their disorder than seizurerelated variables [23 24 25 26]. Illness beliefs have also been shown to predict outcome in patients with medically unexplained neurological symptoms [27]. Patients' illness perceptions are a key feature of the self-regulation model.…”
Section: Discussionmentioning
confidence: 99%
“…These are: timeline acute/chronic-the belief about the chronicity of illness, consequence-the expected adverse effects and outcomes; timeline cyclical-the day to day variability of symptoms; personal control-the degree to which symptoms can be self-controlled; treatment control-the degree to which symptoms can be helped with treatment; illness coherence-understanding about symptoms; emotional representations-degree of distress caused by symptoms. Each question is answered on a 1-5 Likert scale, and subscores for each of domain are calculated [22].…”
Section: The Revised Illness Perception Questionnaire (Ipq-r)mentioning
confidence: 99%